Pengaruh Teknik Vulva Hygiene terhadap Jumlah Kuman Vulva pada Ibu Nifas di BPM Kota Bandar Lampung - Nelly Indrasari; Purwati Purwati (Politeknik Kesehatan Tanjung Karang, 2017)
The case of maternal mortality in Bandar Lampung city in 2013 is 19 cases, in 2014 there are 7 cases and all died during childbirth and there are 19 cases of maternal death by 2015. (Profile of Lampung Province Health Office 2014). Research Objectives to Detect the Influence of Vulva Hygiene Technique on Number of Vulva Germs In Nifas Mother In BPM Bandar Lampung City Year 2016. This research method using quasi-experiment design. This study compares between treated groups and control groups. Treatment group 1 was treated with vulvar hygiene by using 1 cotton, group 2 using 3 kinds of cotton, group 3 using 5 cotton and control group without treatment. Population in this research is mother Nanyang checking his health at BPM in Bandar Lampung city at the time of research. The sample of respondent's research is 120. Data collection with Teradata is done as much as 1 time then done culture and examination in a local laboratory. Data were processed and analyzed by independent T-test. The result showed that the average number of germs was 2277,37 germs (95% CI 7140,59-38402,16) with standard deviation 65553,94 germs. The lowest number of germs and pathogen bacteria still 0.35% of respondents on the vulva hygiene of a cotton with a duration of 26 days. The result of analysis with cruciate Wallis test is 3,498. Looking at the statistics of the table by looking at the Chi-square table, for df (degrees of freedom)=3 and the significance level (α) = 5%, then obtained statist table 2.32. Because of the count statistic (2.32> 0.321), then Ho accepted, or no significant difference (significant). The research unit can utilize and apply vulva hygiene technique with antiseptic, so it can prevent the occurrence of infection in the postpartum mother.